Pharyngeal sense organs drive robust sugar consumption in Drosophila. - LeDue, E.E.; Chen, Y.C.; Jung, A.Y.; Dahanukar, A.; Gordon, M.D. (Nature communications, 2015)
The fly pharyngeal sense organs lie at the transition between external and internal nutrient-sensing mechanisms. Here we investigate the function of pharyngeal sweet gustatory receptor neurons, demonstrating that they express a subset of the nine previously identified sweet receptors and respond to stimulation with a panel of sweet compounds. We show that pox-neuro (poxn) mutants lacking taste function in the legs and labial palps have intact pharyngeal sweet taste, which is both necessary and sufficient to drive preferred consumption of sweet compounds by prolonging ingestion. Moreover, flies putatively lacking all sweet taste show little preference for nutritive or non-nutritive sugars in a short-term feeding assay. Together, our data demonstrate that pharyngeal sense organs play an important role in directing sustained consumption of sweet compounds, and suggest that post-ingestive sugar sensing does not effectively drive food choice in a simple short-term feeding paradigm.